2019
DOI: 10.1111/jen.12620
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phagostimulants on effectiveness of OMRI‐listed insecticides used for control of spotted‐wing drosophila (Drosophila suzukii Matsumura)

Abstract: Spotted‐wing drosophila, Drosophila suzukii Matsumura, is an invasive pest in the United States that causes considerable damage to fruit crops. It is responsible for many millions of dollars of revenue loss. The female D. suzukii has a heavily sclerotized ovipositor and can lay eggs in ripening or ripe fruit. The arrival of this invasive species has disrupted existing integrated pest management programmes, and growers rely on repeated insecticide applications to protect fruit. Organic growers have few chemical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 39 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…Studies about the use of yeasts in control strategies are based on different methods, such as washing the cells from Petri dishes with different sugar-containing liquids (Noble et a. 2019), revitalizing active dry yeast with sugar solution (Knight et al 2015;Roubos et al 2019) and often adjusting the cell number (Mori et al 2016). Since nutrients present in the substrate influence yeast metabolism and therefore the availability of nutrients for the SWD in a yeast-based diet, a microbiological cost-effective commercial medium (PDB) was chosen, and both intra-and extracellular compounds were analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies about the use of yeasts in control strategies are based on different methods, such as washing the cells from Petri dishes with different sugar-containing liquids (Noble et a. 2019), revitalizing active dry yeast with sugar solution (Knight et al 2015;Roubos et al 2019) and often adjusting the cell number (Mori et al 2016). Since nutrients present in the substrate influence yeast metabolism and therefore the availability of nutrients for the SWD in a yeast-based diet, a microbiological cost-effective commercial medium (PDB) was chosen, and both intra-and extracellular compounds were analyzed separately.…”
Section: Discussionmentioning
confidence: 99%
“…The biology of SWD makes it difficult to develop an effective control strategy (Cini et al 2012;Sial et al 2019) to avoid severe economic losses (De Ros et al 2013). As a control strategy against SWD, suitable yeasts can be used as adjuvants in insecticide sprays to increase ingestion in attract-and-kill formulations based on the association of attractant yeasts and an insecticide (Andreazza et al 2017;Knight et al 2015;Noble et al 2019;Roubos et al 2019). To date, insecticides were registered against SWD, and technical strategies, such as exclusion netting, were applied to control this pest (Beers et al 2011;Leach et al 2016.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, laboratory assays also reported that combinations of spinosad and H. uvarum increased D. suzukii mortality relative to the insecticide alone 78 . In contrast to these studies, recent field and laboratory assessments found that adding S. cerevisiae to various organic insecticides did not improve control of D. suzukii in either semi-field or laboratory assays, a difference that may reflect variation in D. suzukii ’s physiological status between studies 79 .…”
Section: Discussionmentioning
confidence: 70%
“…Roubos et al () found that all three adjuvants tested, which included alcohol ethoxylate, poly‐1‐p‐menthene and polyether‐polymethylsiloxane‐copolymer polyether (PEPMS), increased the mortality of some insecticides against D. suzukii populations and that both alcohol ethoxylate and poly‐1‐p‐menthene caused some mortality when used alone. In contrast, adding sucrose or sucrose + yeast at a concentration of 0.36% to selected organic insecticides did not increase the mortality of D. suzukii (Roubos et al, ). Therefore, it is important to determine what effects both the addition of adjuvants and phagostimulants might have on natural enemy populations.…”
Section: Introductionmentioning
confidence: 98%
“…Previous research has indicated that azadirachtin + pyrethrins, Chromobacterium subtsugae , and sabadilla alkaloids cause some mortality in D. suzukii populations and could be useful in rotations with spinosad. The addition of both adjuvants (Roubos et al, ) and phagostimulants (Roubos et al, ) has been proposed to increase the efficacy of these organic insecticides. Roubos et al () found that all three adjuvants tested, which included alcohol ethoxylate, poly‐1‐p‐menthene and polyether‐polymethylsiloxane‐copolymer polyether (PEPMS), increased the mortality of some insecticides against D. suzukii populations and that both alcohol ethoxylate and poly‐1‐p‐menthene caused some mortality when used alone.…”
Section: Introductionmentioning
confidence: 99%